Mutation in the SLC37A4 gene of glycogen storage disease type Ib in 15 families of the mainland of China - Qiu, Zheng-qing (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2011)
OBJECTIVE: Glycogen storage disease type Ib (GSDIb, MIM: 232220) is an autosomal recessive inborn error of metabolism caused by deficiency of the glucose-6-phosphate translocase. The clinical manifestations include symptoms and signs of both the typical GSDIa, including hepatomegaly, fasting hypoglycemia, lactic acidemia and hyperlipidemia, and the dysfunction of neutrophils of recurrent infection and neutropenia. More than 84 mutations have been identified since the discovery of the SLC37A4 gene as the disease causing gene. Up to date, 5 mutations in 4 Chinese patients were reported from Hong Kang and Taiwan. In order to see the spectrum of the SLC37A4 gene mutations and the correlation between genotype and phenotype in patients with GSDIb of the mainland of China, the authors investigated 17 GSDIb patients from 15 families in this study